2018
DOI: 10.1007/s12975-018-0665-4
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Exerts a Whole-Brain Protective Property by Promoting M1? Microglia Quiescence After Experimental Subarachnoid Hemorrhage in Mice

Abstract: Subarachnoid hemorrhage (SAH) is a neurologically destructive stroke in which early brain injury (EBI) plays a pivotal role in poor patient outcomes. Expanding upon our previous work, multiple techniques and methods were used in this preclinical study to further elucidate the mechanisms underlying the beneficial effects of apolipoprotein E (ApoE) against EBI after SAH in murine apolipoprotein E gene-knockout mice (Apoe, KO) and wild-type mice (WT) on a C57BL/6J background. We reported that Apoe deficiency resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 54 publications
1
49
0
Order By: Relevance
“…Overall, APOE tends to maintain BBB integrity and promote neurological recovery. While APOE-deficiency provokes BBB dysfunction, exogenously administered APOE or its mimetic peptides preserve BBB integrity in experimental studies [197][198][199][200][201][202][203].…”
Section: The Bbb Integrity-promoting Effects Of Astrocytesmentioning
confidence: 99%
“…Overall, APOE tends to maintain BBB integrity and promote neurological recovery. While APOE-deficiency provokes BBB dysfunction, exogenously administered APOE or its mimetic peptides preserve BBB integrity in experimental studies [197][198][199][200][201][202][203].…”
Section: The Bbb Integrity-promoting Effects Of Astrocytesmentioning
confidence: 99%
“…Frequently, microglia are redeemed to exist in a resting status (M0). However, upon activation, they are transformed into two different phenotypes (M1 and M2) with distinct physiological functions [6,7]. M1 phenotype microglia are pro-inflammatory as they secrete inflammatory molecules, including IL-1β, IL-6, and TNF-α, which are greatly detrimental to the brain tissues [8].…”
Section: Introductionmentioning
confidence: 99%
“…In endovascular perforation SAH models using adhesion molecule knockout mice, it was demonstrated that SAH resulted in early intravascular inflammation with the recruitment of circulating neutrophils to the vessel/brain interface and that the inhibition of neutrophilendothelial interaction prevented systemic inflammation from accumulating and activating microglia to cause neuronal cell death [19]. Extravasated blood components such as thrombin, platelets, and leukocytes also activate microglia, which is an important mechanism to produce proinflammatory cytokines, matricellular proteins, and oxidative stress, causing EBI in a mouse endovascular perforation model [20,21]. At 24 h after experimental SAH by endovascular perforation in rats, magnetic resonance imaging studies showed that more severe SAH caused a more frequent and larger cerebral infarction, where fibrinogen/fibrin-stained microthromboses were histologically found [22].…”
mentioning
confidence: 99%